2016
DOI: 10.1039/c5cy01401h
|View full text |Cite
|
Sign up to set email alerts
|

Pd/C catalysts based on synthetic carbons with bi- and tri-modal pore-size distribution: applications in flow chemistry

Abstract: Synthetic carbons with hierarchical mesopores are promising for developing new catalysts for intensified continuous-flow catalysis in structured reactors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…5 nm (ref. [32][33][34]), with glass wool placed at each end of the chamber to hold the catalyst bed in place. The liquid and gas streams were preheated to the reaction temperature in an upfront static mixer (length = 6 cm).…”
Section: Catalytic Performance Evaluationmentioning
confidence: 99%
“…5 nm (ref. [32][33][34]), with glass wool placed at each end of the chamber to hold the catalyst bed in place. The liquid and gas streams were preheated to the reaction temperature in an upfront static mixer (length = 6 cm).…”
Section: Catalytic Performance Evaluationmentioning
confidence: 99%
“…The catalyst was based on PdNP onto tri-modal (micro, meso), hierarchical porous synthetic carbon [152]. No catalyst deactivation was detected over 5 hours continuous runs (333 K, 1 bar H 2 ).…”
Section: Reviewmentioning
confidence: 99%
“…Specialist catalyst development has often been targeted towards chemoselectivity. Fan et al have shown that the Pd/triC catalyst was selectively reduced alkyne groups over nitro, bromo, and aldehyde groups [50]. While Rathi's palladium nanoparticles supported on maghemite were effective in reducing nitroarenes, azides, and alkenes in good to excellent yields [52].…”
Section: New Advances In Hydrogenation Processes -Fundamentals and Apmentioning
confidence: 99%